2023
DOI: 10.12775/jehs.2023.35.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Withania somnifera (Ashwagandha) supplementation in obesity

Alicja Nowak,
Klaudia Bogusz,
Natalia Baran
et al.

Abstract: Introduction and purpose: Ashwagandha (fam. Solanaceae) also known as Withania somnifera, is an herb commonly used in traditional Ayurvedic medicine. It is sometimes called Indian ginseng or winter cherry and it is used for its extensive health benefits for millennia as a Rasayana. Ashwagadha supplementation is playing an increasing role not only as an adaptogen, but is beneficial in the context of health in individuals struggling with obesity. This is a growing field of research and the aim of this brief revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…While acknowledging its promising effects, the review highlighted the need for extensive, long-term clinical trials to conclusively validate its efficacy and safety. 18 A recent systematic review published in a scientific jour-nal specializing in herbal medicine found the evidence supporting Ashwagandha's effectiveness in managing diabetes to be weak. The review highlights the need for further research to fully explore its potential benefits in this area.…”
Section: Ashwagandha (Withania Somnifera (L) Dunal)mentioning
confidence: 99%
“…While acknowledging its promising effects, the review highlighted the need for extensive, long-term clinical trials to conclusively validate its efficacy and safety. 18 A recent systematic review published in a scientific jour-nal specializing in herbal medicine found the evidence supporting Ashwagandha's effectiveness in managing diabetes to be weak. The review highlights the need for further research to fully explore its potential benefits in this area.…”
Section: Ashwagandha (Withania Somnifera (L) Dunal)mentioning
confidence: 99%